Bibliometric Mapping of Digital Transformation in Government Services - Loso Judijanto (Eastasouth Institute, 2025)
The rapid advancement of digital technologies has fundamentally reshaped the way governments design, deliver, and manage public services, positioning digital transformation as a strategic priority in contemporary public administration. Alongside this transformation, scholarly interest in digital government services has expanded rapidly, resulting in a fragmented and diverse body of literature. This study aims to systematically map the intellectual structure, thematic evolution, and collaborative patterns of research on digital transformation in government services through a bibliometric approach. Using publication data retrieved from the Scopus database covering the period 2003–2023, this study employs VOSviewer to conduct keyword co-occurrence analysis, co-authorship analysis, institutional collaboration mapping, and country-level collaboration analysis. The findings reveal that digital transformation serves as the central integrative concept connecting governance reform, public service delivery, decision-making, and advanced technologies such as artificial intelligence. Temporal analysis indicates a clear shift from early technology-oriented themes toward service-centric, data-driven, and intelligent governance paradigms. Collaboration networks further demonstrate the globalization of digital government research, with strong contributions from North America, Europe, and rapidly growing participation from Asia and emerging economies. Overall, this study provides a comprehensive overview of the knowledge landscape, highlights emerging research frontiers, and offers insights to guide future academic inquiry and policy development in digital government services.